New Challenges for the Ethics of Anthropological Practice: Workshop of the Czech Association for Social Anthropology, 19 March 2018, Scouts’ Institute in Prague - Kissová, Blanka (Lidé města, 2018)
Entering the location of a researched field always carries with it a whole range of issues pertaining to the responsible approach to the question at hand and to its conveyors – the informants, or the participants of the research. The anthropologist, i.e. the individual carrying out the research, attempts to understand a phenomenon, as well as to find answers to both questions posed in advance and to those discovered during the research itself. They enter a space where concrete people live, and the anthropologist’s movements in this terrain may have a significant impact on the lives of these individuals or of these communities. In any case, they inform, or in the very least should inform, not just their colleagues, but also the general public of their findings. They are thus the medium that presents certain discoveries and interpretations, that creates theories, or that supports or, on the contrary, dismisses already existing theories.